Customer Satisfaction Is Effected By The Quality Of Service: A Case Study Indonesian - et.al, MuhammadAfifi Rahman , AmirulAffanRosyidi (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to determine and analyze the effect of service quality indicators in measurement using Tangible, Emphaty, Reliability, Responsiveness, and Assurance on Banking Customer Satisfaction in Indonesia.This research uses quantitative methods that are descriptive and tends to analyze using an inductive approach. This type of research uses Explanatary Research, the study population uses banking customers. The data collection method in this study is to spread questions with the right target, the questionnaire in this study has requirements that must be met: The questions are factual, the questions are opinion, the questions are self-perception.The findings in this study explain that service quality affects customer satisfaction, the results of statistical tests with t test can be concluded that service quality has an influence on banking customer satisfaction.